Dossier Communication des primates humains et non humains : à la recherche des origines du langage – Introduction générale - Adrien Meguerditchian (Revue de Primatologie)
Human language is a unique and extraordinary communicative system involving many cognitive features. While the contributions of primatologists have historically poorly considered the question of its origins, there is a renewed interest in the scientific community regarding the investigations on primate communication systems and their potential continuities with the properties of human language. This special section of the journal "Revue de primatologie" aims at compiling the recent findings on these researches through a multidisciplinary approach (ethology, comparative psychology, neurosciences), and thus to discuss the potential precursors of language in our ancestors.